Kecemasan Akademik sebagai Prediktor Kualitas Tidur Mahasiswa Keperawatan dalam Persiapan Ujian Objective Structured Clinical Examination (Osce) - Marista Fiana; Riki ukhtul fitri fitri; Ade Komariah; Reni Muhka; Nova Maulana; Rastia Ningsih; Nova Listya Wahaningtyas; Risnandhia Risnandhia; Fevi Pahila; Hernawati Hernawati; Fatimah Wahab Aliun (Universitas Malahayati Lampung, 2026)
ABSTRACT The Objective Structured Clinical Examination (OSCE) is an evaluation method used to assess students' clinical competence. The demands of the exam trigger psychological pressure and increase students' anxiety. The purpose of this study was to determine the relationship between anxiety levels and sleep quality among fifth-year nursing students at Bina Bangsa University in preparation for the OSCE. This study was a quantitative correlational study with a cross-sectional approach. The research population consisted of fifth-year undergraduate nursing students at Bina Bangsa University who were going to take the OSCE exam. The sample size was 113 respondents, using total sampling technique. Data analysis was performed using Spearman's rank correlation test. The results showed a significant relationship with a p-value of 0.002 (P0.05) and a correlation coefficient of 0.305, indicating a weak to moderate relationship between anxiety levels and sleep quality among students facing the OSCE exam. Keywords: Anxiety, Sleep Quality, Objective Structured Clinical Examination (OSCE). ABSTRAK Objective Structured Clinical Examination (OSCE) merupakan metode evaluasi untuk menilai kompetensi klinik mahasiswa, tuntutan ujian menjadi pemicu yang menimbulkan tekanan psikologis dan meningkatkan kecemasan mahasiswa.Tujuan penelitian ini untuk mengetahui hubungan tingkat kecemasan terhadap kualitas tidur pada mahasiswa program studi sarjana keperawatan tingkat V Universitas Bina Bangsa dalam menghadapi OSCE. Jenis Penelitian ini adalah kuantitatif korelasional dengan pendekatan cross sectional. Populasi penelitian yaitu Mahasiswa Program Studi Sarjana Keperawatan Tingkat V di Universitas Bina Bangsa yang akan mengikuti ujian OSCE, jumlah sampel sebanyak 113 responden, teknik sample total sampling. Analisis data menggunakan uji korelasi Spearmen Rank. Hasil penelitian menunjukan hubungan yang signifikan dengan p value 0,002 (P0,05) dengan nilai koefisien korelasi 0,305 menunjukkan kekuatan hubungan dalam kategori lemah hingga sedang antara hubungan tingkat kecemasan terhadap kualitas tidur pada mahasiswa dalam menghadapi ujian OSCE. Kata Kunci: Kecemasan, Kualitas Tidur, Objective Structured Clinical Examination (OSCE).